Dance Troupe Celebrated as Innovative (Raton Range Raton, NM, 1993)
The article is a review of the Ririe-Woodbury Dance Company and about how it came to be.
Newspaper Article + Photograph of the Ririe-Woodbury Dance Company
Master list item #: 31
File location is in the Raton file Cabinet
Keywords: Ririe-Woodbury Dance Company -- Dance Troupe; Dance Performance; Arts and Humanities Council; Dance Troupe; Raton, New Mexico